Diamond / metal high thermal conductivity metal-based composite material for electronic packaging and preparation method thereof

By annealing heat treatment of the diamond surface chrome plating and graphene-coated metal powder, the interface combination between diamond and metal matrix is ​​optimized, and the problem of low thermal conductivity of existing diamond/metal electronic packaging materials is solved, achieving efficient heat dissipation effect.

CN119040681BActive Publication Date: 2025-03-14陕西陕煤启远科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411532095.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-14
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing diamond/metal electronic packaging materials have low thermal conductivity and cannot meet the demand for efficient heat dissipation of high-power electronic components.

Method used

By annealing heat treatment of the diamond surface chrome plating and graphene-coated metal powder, a "carbon-chromium" and "metal-carbon" core-shell structure is formed, and the interface combination between diamond and metal matrix is ​​optimized.

Benefits of technology

The thermal conductivity of composite materials has been significantly improved to reach 382~561W/(m·K), meeting the demand for efficient heat dissipation of microelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119040681B_ABST
    Figure CN119040681B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal-based composite material preparation, discloses a diamond / metal high thermal conductivity metal-based composite material for electronic packaging and a preparation method, chrome-plating treatment is performed on the diamond surface to obtain chrome-plated diamond powder; the matrix metal powder and graphene are evenly mixed to obtain graphene-coated metal powder; the chrome-plated diamond powder and the graphene-coated metal powder are annealed and heat-treated respectively, and the heat-treated powders are mixed and sintered. In the present invention, by chrome-plating on the diamond surface, a "carbon-chromium" core-shell structure is formed, and a "metal-carbon" core-shell structure is formed by using graphene-coated metal, thereby converting the original "metal-carbon" interface of the matrix and the reinforcement into a "carbon-chromium" interface. After hot pressing and sintering the "carbon-chromium" interface to form a reaction bonding interface, the reinforcement and the matrix metal interface bonding strength can be improved, the purpose of improving the thermal conductivity of the composite material is achieved, and the demand for efficient heat dissipation of microelectronic devices is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal matrix composite material preparation, and relates to a diamond / metal high thermal conductivity metal matrix composite material for electronic packaging and a preparation method thereof. Background Art

[0002] As electronic technology develops rapidly towards high density, high speed, high power and miniaturization, the heat generated by electronic components has increased dramatically. Heat dissipation has become one of the technical bottlenecks faced by the development of the electronic information industry. Especially in the high-tech field with high-power insulated gate bipolar transistors (IGBT), microwave, radio frequency, optoelectronics and other devices as typical applications, and the defense technology field with active phased array radar, high-power semiconductor lasers and other typical applications, there is a more urgent demand for efficient heat dissipation materials. Therefore, the research and development of new thermal management materials with high thermal conductivity has become the key to improving the performance and reliability of electronic components.

[0003] Traditional electronic packaging materials such as Kovar alloy, tungsten copper alloy and molybdenum copper alloy have various problems in their application in today's electronic field. For example, the thermal conductivity of Kovar alloy is too low (less than 20W / m·K), so it can only be used in low power density devices; tungsten copper alloy and molybdenum copper alloy have an adaptive thermal expansion coefficient and a thermal conductivity of about 200 W / m·K, but their specific gravity is large and they are gradually unable to meet the requirements of mobile devices and aerospace fields. Silicon carbide / aluminum (SiC P / Al) and Silicon / Aluminum (Si P The third-generation electronic packaging materials represented by Oxygen-Free Copper (Oxygen-Free Copper) composite materials have an adjustable thermal expansion coefficient, but their thermal conductivity is lower than that of oxygen-free copper, which cannot meet the needs in the fields of high-power semiconductor lasers and third-generation semiconductor device packaging.

[0004] Diamond is the material with the highest thermal conductivity in nature. Its thermal conductivity is 5 times that of copper (up to 2000W / m·K). It has great advantages in the field of heat conduction and heat dissipation. The fourth generation of electronic packaging materials represented by diamond / aluminum (Diamond / Al) and diamond / copper (Diamond / Cu) composite materials have become a hot spot in research and development. However, due to the poor wettability between diamond and metal, the bonding effect at the interface of diamond / metal composite materials is poor, which affects the overall thermal conductivity of the material. Therefore, optimizing the interface bonding between diamond and metal matrix has become the key to improving the thermal conductivity of composite materials.

[0005] As the density of microelectronic devices and modules continues to increase and the size continues to shrink, the heat flux density per unit volume continues to rise, and the heat dissipation problem has become one of the technical bottlenecks faced by the development of the electronic information industry. Especially in high-tech and high-power fields such as high-power semiconductor lasers, active phased array radars, and IGBT modules, solving the heat dissipation problem is more urgent, which has also promoted the development of a new generation of high thermal conductivity electronic packaging materials. Summary of the invention

[0006] In order to overcome the problem of low thermal conductivity of diamond / metal electronic packaging materials in the prior art, the purpose of the present invention is to provide a diamond / metal high thermal conductivity metal-based composite material for electronic packaging and a preparation method thereof, wherein the composite material prepared by the method has high thermal conductivity.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a diamond / metal high thermal conductivity metal-based composite material for electronic packaging, comprising the following steps:

[0009] Performing chrome plating on the surface of diamond to obtain chrome-plated diamond powder;

[0010] The base metal powder and the graphene are mixed evenly to obtain the graphene-coated metal powder;

[0011] Performing annealing heat treatment on the chrome-plated diamond powder and the graphene-coated metal powder respectively, and mixing the heat-treated powders to obtain a mixed powder;

[0012] The mixed powder is hot pressed and sintered to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0013] A further improvement of the present invention is that the diamond powder is vacuum dried before the diamond surface is chrome plated; and the base metal powder and the graphene are vacuum dried before the base metal powder and the graphene are evenly mixed.

[0014] A further improvement of the present invention is that the chrome-plated diamond powder includes forming a chrome-plated layer with a thickness of 1 to 2 μm on the surface of the diamond.

[0015] A further improvement of the present invention is that the base metal powder is aluminum powder or copper powder.

[0016] A further improvement of the present invention is that the amount of graphene used is 0.2wt%~1wt% of the base metal powder;

[0017] The base metal powder and graphene are evenly mixed by ball milling.

[0018] A further improvement of the present invention is that the conditions for annealing the chrome-plated diamond powder are: the vacuum degree is less than 1×10 -3 Pa, annealing temperature is 300~350℃, annealing time is 1h~2h;

[0019] The conditions for annealing the graphene-coated metal powder are as follows: the vacuum degree is less than 1×10 -3 Pa, annealing temperature is 200~250℃, and annealing time is 2h~3h.

[0020] A further improvement of the present invention is that the conditions for hot pressing sintering are: sintering temperature is 500-1000° C., pressure is 20-30 MPa, and time is 20-40 min.

[0021] A further improvement of the present invention is that the temperature is increased to 500-1000° C. at a heating rate of 8-10° C. / min.

[0022] A further improvement of the present invention is that, taking the total volume of the base metal powder and diamond as 100%, the volume percentage of the base metal powder is 30% to 70%, and the amount of graphene added is 0.2wt% to 1wt% of the base metal powder.

[0023] A diamond / metal high thermal conductivity metal-based composite material for electronic packaging, wherein the thermal conductivity of the composite material is 382-561 W / (m·K).

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] Since metallic chromium is a strong carbide-forming element, it has a strong affinity with carbon and can react to form stable carbides. Therefore, the present invention chooses to plate chromium on the surface of diamond as a reinforcement to change the surface of diamond into a "carbon-chromium" core-shell structure. Since graphene is a new material in which carbon atoms connected by sp² hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure, it not only has good mechanical properties (such as tensile strength up to 130GPa, while maintaining good toughness), but also has ultra-high thermal conductivity (the thermal conductivity of defect-free single-layer graphene is as high as 5300 W / m·K), so the present invention uses graphene to coat metal to form a "metal-carbon" core-shell structure. By plating diamond with chromium and coating the matrix metal with graphene, the original "metal-carbon" interface between the matrix and the reinforcement is transformed into a "carbon-chromium" interface. Then, the chromium-plated diamond powder is annealed and heat-treated to rearrange the atoms inside the coating, thereby releasing internal stress, improving the stability and durability of the coating, and facilitating the formation of the composite material interface and the improvement of material performance. The "carbon-chromium" interface is then hot-pressed and sintered to form a reactive bonding interface, which can enhance the bonding strength between the reinforcement and the matrix metal interface, ultimately achieving the goal of improving the thermal conductivity of the composite material and meeting the needs of microelectronic devices for efficient heat dissipation.

[0026] Furthermore, the base metal powder, diamond, and graphene are vacuum dried to remove moisture and gas impurities in the raw materials, which can reduce the oxidation and corrosion of the raw materials caused by moisture, as well as the pores and bubbles that may be formed during the sintering process, thereby improving the density and physical properties of the composite materials.

[0027] Furthermore, during the ball milling process, graphene and metal powder will be subjected to mechanical stress and produce internal stress and defects. Annealing heat treatment can release and repair these stresses and defects, and can also promote further dispersion and uniform distribution of graphene in the metal matrix, thereby improving the overall performance of the composite material.

[0028] Furthermore, taking into account the material composition of the base metal, the particle size of the material, the melting point of the metal, the equipment working conditions and the final material properties, the selected sintering temperature is 500-1000°C, i.e. 0.75Tm-0.95Tm, where Tm is the melting point of the base metal. Considering the large difference in the inherent properties of the base metal and diamond, especially the large difference in the thermal expansion coefficient, the temperature is slowly increased at a heating rate of 8-10°C / min during hot pressing sintering, which helps to gradually release and balance the internal stress of the material, reduce the risk of cracking and deformation during the sintering process, and thus improve the microstructure and performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart of a method for preparing a composite material. DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.

[0031] Graphene is a new material in which carbon atoms connected by sp² hybridization are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. It not only has excellent mechanical properties (such as tensile strength up to 130GPa while maintaining good toughness), but also has ultra-high thermal conductivity (the thermal conductivity of defect-free single-layer graphene is as high as 5300 W / m·K). Therefore, in the present invention, graphene is coated with metal to form a "carbon-metal" structure, and chrome is plated on the diamond surface to form a "carbon-chromium" structure. After hot pressing and sintering, the matrix diamond and the reinforcement can form a reactive bonding interface, and finally the purpose of improving the thermal conductivity of the composite material is achieved.

[0032] The present invention discloses a method for preparing a diamond / metal high thermal conductivity metal-based composite material for electronic packaging, which improves the interface bonding between diamond and base metal by using a dual optimization method of chrome plating on the diamond surface and graphene-enhanced base metal. The chrome-plated diamond is prepared by a DC magnetron sputtering method and subjected to vacuum annealing heat treatment, the graphene-coated metal powder (such as aluminum powder or copper powder, etc.) is prepared by a ball milling method and subjected to vacuum annealing heat treatment, and then the treated chrome-plated diamond powder and the graphene-coated metal powder are mixed, and a vacuum hot pressing sintering method is used to finally prepare a metal-based composite material with chrome-plated diamond and graphene dual reinforcement. The method can optimize the interface bonding between the base and the reinforcement, and achieve the purpose of improving the thermal conductivity of the composite material.

[0033] For details, see Figure 1 The preparation method of the diamond / metal high thermal conductivity metal matrix composite material for electronic packaging mainly comprises the following steps:

[0034] (1) Preparation of materials

[0035] Determine the amount of base metal powder (such as aluminum powder or copper powder, etc.), reinforcement diamond powder and graphene by calculation;

[0036] In the present invention, taking the volume percentage of base metal powder and reinforcement as 100%, the volume percentage of base metal powder is 30%-70%, the volume percentage of reinforcement is 30%-70%, and the amount of graphene added is 0.2wt%-1wt% of the base metal powder.

[0037] (2) Drying

[0038] In a vacuum oven, the temperature is kept at 60-80°C for 5 hours to dry and exhaust the base metal powder, the reinforcement diamond powder and the graphene;

[0039] (3) Chrome plating of reinforcement and graphene-coated metal powder

[0040] The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method. The chromium target used for sputtering has a chromium content of >99.9%. The thickness of the chromium plated layer formed on the surface of the diamond powder is about 1-2 μm, thereby obtaining chromium-plated diamond powder.

[0041] Using a ball milling method, a dried base metal powder (such as aluminum powder or copper powder) is poured into a ball mill, and then 0.2wt% to 1wt% of graphene is added to the base metal for ball milling for 8 hours to form a metal powder with the outer surface coated with graphene, that is, a graphene-coated metal powder is obtained;

[0042] (4) Heat treatment of chrome-plated diamond powder and graphene-coated metal powder

[0043] The chrome-plated diamond powder is annealed in a vacuum furnace with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 300~350℃, annealing time is 1h~2h;

[0044] The graphene-coated metal powder was annealed in a vacuum furnace with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 200~250℃, annealing time is 2h~3h;

[0045] During the diamond chrome plating process, residual internal stress may be generated between the diamond and chrome plating layers and inside the plating layers. If these internal stresses are not released in time, they may affect the stability of the plating layer, and ultimately affect the thermal conductivity of the composite material. Therefore, annealing heat treatment of chrome-plated diamond powder can rearrange the atoms inside the plating layer, thereby releasing internal stress, improving the stability and durability of the plating layer, and contributing to the formation of the composite material interface and the improvement of material performance.

[0046] (5) Mixing

[0047] The chrome-plated diamond powder and graphene-coated metal powder prepared in step (4) are added into a powder mixer and stirred for about 2 hours to obtain a mixed powder;

[0048] (6) Moulding

[0049] The mixed powder in step (5) is placed into a hot pressing mold, and the mold is then placed into a vacuum hot pressing furnace;

[0050] (7) Hot pressing

[0051] First, the vacuum hot press furnace was evacuated to less than 0.1 Pa, and then argon was filled into the furnace until the vacuum pressure was 1.5×10 4 Pa~2×10 4 Pa, hot pressing sintering is used for sintering, the sintering temperature is 500-1000℃ (depending on the base metal), the heating rate is 8-10℃ / min, the hot pressing pressure is 20-30MPa, and the heat preservation and pressure holding time is 20-40min;

[0052] (8) Demolding after taking out of oven

[0053] After the hot pressing is completed, the mold is naturally cooled to room temperature, and the mold is taken out for demoulding to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0054] The following are specific embodiments.

[0055] Example 1

[0056] Step 1: According to the diamond / aluminum composite material with a diamond volume percentage of 50%, the required aluminum powder 135g (-100 mesh high-purity aluminum powder), diamond powder 175.5g (about 200μm artificial single crystal diamond) and graphene 0.54g (0.4wt% of the aluminum powder) are calculated;

[0057] Step 2: Place aluminum powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0058] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plating layer is about 1 μm, to obtain chromium-plated diamond powder;

[0059] Using a ball milling method, the dried aluminum powder is poured into a ball milling jar, and then the dried graphene is added and ball milled for 8 hours to form aluminum powder with the outer surface coated with graphene, that is, graphene-coated metal powder is obtained;

[0060] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 300 °C, annealing time is 1 h;

[0061] The graphene-coated aluminum powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 200 °C, annealing time is 2 h;

[0062] Step 5: Pour the chrome-plated diamond powder and graphene-coated aluminum powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0063] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0064] Step 7: Sintering is performed by hot pressing method. The furnace is evacuated to less than 0.1 Pa, and then filled with argon gas until the vacuum pressure in the furnace is 1.7×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 550℃, the heating rate was 8℃ / min, the hot pressing pressure was 25MPa, and the holding time was 30min;

[0065] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain the prepared blank, which is the diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0066] Example 2

[0067] Step 1: According to the diamond / aluminum composite material with a diamond volume percentage of 60%, the required aluminum powder 135g (-100 mesh high-purity aluminum powder), diamond powder 263.25g (artificial single crystal diamond of about 200μm) and graphene 0.54g (0.4wt% of the aluminum powder) are calculated;

[0068] Step 2: Place aluminum powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0069] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plating layer is about 1 μm, to obtain chromium-plated diamond powder;

[0070] Using a ball milling method, the dried aluminum powder is poured into a ball milling jar, and then the dried graphene is added and ball milled for 8 hours to form aluminum powder with the outer surface coated with graphene, that is, graphene-coated metal powder is obtained;

[0071] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 300 °C, annealing time is 1 h;

[0072] The graphene-coated aluminum powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 220℃, annealing time is 3h;

[0073] Step 5: Pour the chrome-plated diamond powder and graphene-coated aluminum powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0074] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0075] Step 7: First, evacuate the furnace to a vacuum pressure of less than 0.1 Pa, and then fill it with argon until the vacuum pressure in the furnace is 1.8×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 580℃, the heating rate was 8℃ / min, the hot pressing pressure was 28MPa, and the holding time was 35min;

[0076] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0077] Example 3

[0078] Step 1: According to the diamond / copper composite material with a diamond volume percentage of 50%, the required copper powder 445g (-100 mesh high-purity electrolytic copper powder), diamond powder 175.5g (about 200μm artificial single crystal diamond) and graphene 3.56g (0.8wt% of the copper powder) are calculated;

[0079] Step 2: Place copper powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0080] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plating layer is about 1 μm, to obtain chromium-plated diamond powder;

[0081] The dried copper powder is poured into a ball mill by a ball milling method, and the dried graphene is added and ball milled for 8 hours to form a copper powder whose outer surface is coated with graphene, that is, a graphene-coated metal powder is obtained;

[0082] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 300 °C, annealing time is 2 h;

[0083] The graphene-coated copper powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 200 °C, annealing time is 2 h;

[0084] Step 5: Pour the chrome-plated diamond powder and graphene-coated copper powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0085] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0086] Step 7: First, evacuate the furnace to a vacuum pressure of less than 0.1 Pa, and then fill it with argon until the vacuum pressure in the furnace is 1.6×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 950℃, the heating rate was 8℃ / min, the hot pressing pressure was 25MPa, and the holding time was 30min;

[0087] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0088] Example 4

[0089] Step 1: According to the diamond / copper composite material with a diamond volume percentage of 60%, the required copper powder 296.7g (-100 mesh high-purity electrolytic copper powder), diamond powder 175.5g (about 200μm artificial single crystal diamond) and graphene 2.37g (0.8wt% of the copper powder) are calculated;

[0090] Step 2: Place copper powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0091] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plating layer is about 1 μm, to obtain chromium-plated diamond powder;

[0092] The dried copper powder is poured into a ball mill by a ball milling method, and the dried graphene is added and ball milled for 8 hours to form a metal powder whose outer surface is coated with graphene, that is, a graphene-coated metal powder is obtained;

[0093] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 330 °C, annealing time is 1 h;

[0094] The graphene-coated copper powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 250℃, annealing time is 2h;

[0095] Step 5: Pour the chrome-plated diamond powder and graphene-coated copper powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0096] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0097] Step 7: First, evacuate the furnace to a vacuum pressure of less than 0.1 Pa, and then fill it with argon until the vacuum pressure in the furnace is 1.6×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 980℃, the heating rate was 8℃ / min, the hot pressing pressure was 28MPa, and the holding time was 35min;

[0098] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0099] Example 5

[0100] Step 1: According to the diamond / aluminum composite material with a diamond volume percentage of 30%, the required aluminum powder 135g (-100 mesh high-purity aluminum powder), diamond powder 75.2g (artificial single crystal diamond of about 200μm) and graphene 1.35g (1wt% of the aluminum powder) are calculated;

[0101] Step 2: Place aluminum powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0102] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plating layer is about 1 μm, to obtain chromium-plated diamond powder;

[0103] Using a ball milling method, the dried aluminum powder is poured into a ball milling jar, and then the dried graphene is added and ball milled for 8 hours to form aluminum powder with the outer surface coated with graphene, that is, graphene-coated metal powder is obtained;

[0104] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 300 °C, annealing time is 1 h;

[0105] The graphene-coated aluminum powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 200 °C, annealing time is 2 h;

[0106] Step 5: Pour the chrome-plated diamond powder and graphene-coated aluminum powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0107] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0108] Step 7: Sintering is performed by hot pressing. The furnace is evacuated to a vacuum of less than 0.1 Pa, and then filled with argon until the vacuum pressure in the furnace is 2×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 500℃, the heating rate was 10℃ / min, the hot pressing pressure was 20MPa, and the holding time was 20min;

[0109] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain the prepared blank, which is the diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0110] Example 6

[0111] Step 1: According to the diamond / copper composite material with a diamond volume percentage of 70%, the required copper powder 190.7g (-100 mesh high-purity electrolytic copper powder), diamond powder 175.5g (about 200μm artificial single crystal diamond) and graphene 0.38g (0.2wt% of the copper powder) are calculated;

[0112] Step 2: Place copper powder, diamond powder and graphene in a vacuum oven, keep it at 60-80°C for 5 hours, and dry and exhaust all raw materials;

[0113] Step 3: The surface of the dried diamond powder is chromium plated by a DC magnetron sputtering method, the chromium target used for sputtering has a chromium content of >99.9%, and the thickness of the chromium plated layer is about 2 μm, to obtain chromium-plated diamond powder;

[0114] The dried copper powder is poured into a ball mill by a ball milling method, and the dried graphene is added and ball milled for 8 hours to form a metal powder whose outer surface is coated with graphene, that is, a graphene-coated metal powder is obtained;

[0115] Step 4: Place the chrome-plated diamond powder prepared in step 3 in a vacuum furnace for annealing heat treatment, with a vacuum degree of less than 1×10 -3 Pa, annealing temperature is 350℃, annealing time is 1h;

[0116] The graphene-coated copper powder prepared in step 3 is annealed in a vacuum furnace with a vacuum degree of less than 1×10 - 3 Pa, annealing temperature is 200 °C, annealing time is 2 h;

[0117] Step 5: Pour the chrome-plated diamond powder and graphene-coated copper powder processed in step 4 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0118] Step 6: Place the mixed powder in step 5 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0119] Step 7: First, evacuate the furnace to a vacuum pressure of less than 0.1 Pa, and then fill it with argon until the vacuum pressure in the furnace is 1.5×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 1000℃, the heating rate was 8℃ / min, the hot pressing pressure was 30MPa, and the heat preservation and pressure holding time was 40min;

[0120] Step 8: After step 7 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demolded to obtain a diamond / metal high thermal conductivity metal-based composite material for electronic packaging.

[0121] Comparative Example 1

[0122] Step 1: According to the diamond / aluminum composite material with a diamond volume percentage of 55%, the required aluminum powder of 135g (-100 mesh high-purity aluminum powder) and diamond powder of 214.5g (about 200μm artificial single crystal diamond) are calculated;

[0123] Step 2: Place aluminum powder and diamond powder in a vacuum oven and keep it at 60-80℃ for 5 hours to dry and exhaust all raw materials;

[0124] Step 3: Pour the diamond powder and aluminum powder processed in step 2 into a powder mixer and stir for about 2 hours to obtain a mixed powder;

[0125] Step 4: Place the mixed powder in step 3 into a hot pressing mold, and then place the mold into a vacuum hot pressing furnace;

[0126] Step 5: Sintering is performed by hot pressing method. The furnace is evacuated to less than 0.1 Pa, and then filled with argon gas until the vacuum pressure in the furnace is 1.5×10 4 Pa, sintering was carried out by hot pressing method, the sintering temperature was 560℃, the heating rate was 8℃ / min, the hot pressing pressure was 28MPa, and the holding time was 35min;

[0127] Step 6: After step 5 is completed, the furnace body is cooled naturally to room temperature, the mold is taken out and demoulded to obtain the prepared blank, which is the metal matrix composite material.

[0128] The properties of the composite materials prepared in Examples 1 to 6 are shown in Table 1.

[0129] Table 1 Properties of the composite materials prepared in Examples 1 to 6 and Comparative Example 1

[0130]

[0131] It can be seen from Table 1 that the thermal conductivity of the composite material prepared in the present invention is 382-561 W / (m·K), which is higher than the thermal conductivity of Comparative Example 1.

[0132] The present invention is based on traditional metal-based composite materials for electronic packaging such as diamond / aluminum and diamond / copper. The diamond reinforcement is pre-plated with metal chromium and the base metal is coated with graphene before composite. The base metal and the reinforcement form a reactive bonding interface, which improves the wettability and interface bonding strength between the base metal and the reinforcement, achieves performance improvement of the composite material, and can meet the needs of microelectronic devices for efficient heat dissipation.

[0133] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.

[0134] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

Claims

1. A method for preparing a diamond / metal high thermal conductivity metal-based composite material for electronic packaging, characterized in that: The following steps are involved: Performing chrome plating on the surface of diamond to obtain chrome-plated diamond powder; The base metal powder and the graphene are mixed evenly to obtain the graphene-coated metal powder; Performing annealing heat treatment on the chrome-plated diamond powder and the graphene-coated metal powder respectively, and mixing the heat-treated powders to obtain a mixed powder; The mixed powder is hot pressed and sintered to obtain a diamond / metal high thermal conductivity metal matrix composite material for electronic packaging; The conditions for hot pressing sintering are: sintering temperature is 500-1000°C, pressure is 20-30MPa, and time is 20-40min; Heating to 500-1000°C at a heating rate of 8-10°C / min; The chrome-plated diamond powder includes forming a chrome-plated layer with a thickness of 1 to 2 μm on the surface of the diamond; Taking the total volume of the base metal powder and diamond as 100%, the volume percentage of the base metal powder is 30% to 70%, and the amount of graphene added is 0.2wt% to 1wt% of the base metal powder.

2. The method for preparing the diamond / metal high thermal conductivity metal matrix composite material for electronic packaging according to claim 1, characterized in that: The diamond powder is vacuum dried before the diamond surface is chrome plated; the base metal powder and the graphene are vacuum dried before being evenly mixed.

3. The method for preparing the diamond / metal high thermal conductivity metal matrix composite material for electronic packaging according to claim 1, characterized in that: The base metal powder is aluminum powder or copper powder.

4. The method for preparing the diamond / metal high thermal conductivity metal-based composite material for electronic packaging according to claim 1, characterized in that: The base metal powder and graphene are evenly mixed by ball milling.

5. The method for preparing the diamond / metal high thermal conductivity metal matrix composite material for electronic packaging according to claim 1, characterized in that: The conditions for annealing heat treatment of chrome-plated diamond powder are: vacuum degree is less than 1×10 -3 Pa, annealing temperature is 300~350℃, annealing time is 1h~2h; The conditions for annealing the graphene-coated metal powder are as follows: the vacuum degree is less than 1×10 -3 Pa, annealing temperature is 200~250℃, and annealing time is 2h~3h.

6. A diamond / metal high thermal conductivity metal matrix composite material for electronic packaging prepared according to the method according to any one of claims 1 to 5, characterized in that: The thermal conductivity of the composite material is 382-561 W / (m·K).

Citation Information

Patent Citations

  • Powder metallurgy preparation method of graphene reinforced aluminum-based composite material

    CN112725660A

  • Preparation method of graphene reinforced matrix diamond segment

    CN117600471A